2016
DOI: 10.7860/jcdr/2016/19245.7945
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Re-entry of an Intentionally Replanted Periodontally Compromised Tooth Treated with Platelet Rich Fibrin (PRF): Hopeless to Hopeful

Abstract: A systemically healthy 23-year-old male patient reported to the Department of Periodontics, College of Dental Sciences, Davangere, Karnataka, India with the chief complaint of pain in his upper front tooth since one week which aggravated on biting. Past dental history revealed a self-fall and trauma to the upper front tooth region, two months back. Clinical examination revealed inflamed gingiva, pus exudation, extrusion, Miller's Grade III mobility, pocket depth of 14mm mesio-, mid-and distolabially; 10mm mesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The analysis of research themes showed that IR for periapical diseases gained the most significant attention in publications before 2000, whereas IR for vertical root fractures, 35–39 crown root fractures, 40–43 and periodontic diseases 44–48 gradually became the main theme since 2001. During 2001–2005 and 2010–2015, several materials were used for the management of vertical root fractures with IR, including self‐etching dual‐cure adhesive resin cement, 35,36 calcium‐enriched adhesive resin cement, 49 and 4‐methacryloxyethyl trimellitate anhyride/methacrylate‐tri‐n‐butyl borane (4‐META/MMA‐TBB) resin cement 37–39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of research themes showed that IR for periapical diseases gained the most significant attention in publications before 2000, whereas IR for vertical root fractures, 35–39 crown root fractures, 40–43 and periodontic diseases 44–48 gradually became the main theme since 2001. During 2001–2005 and 2010–2015, several materials were used for the management of vertical root fractures with IR, including self‐etching dual‐cure adhesive resin cement, 35,36 calcium‐enriched adhesive resin cement, 49 and 4‐methacryloxyethyl trimellitate anhyride/methacrylate‐tri‐n‐butyl borane (4‐META/MMA‐TBB) resin cement 37–39 .…”
Section: Resultsmentioning
confidence: 99%
“…Since 2008, an increasing number of studies have evaluated the use of IR for teeth with crown root fractures, 40–43 in some cases with 180‐degree rotation 40,43 . Furthermore, researchers have noted that the use of biomaterials (e.g., leukocyte‐platelet‐rich fibrin) with IR seems to be beneficial for rescuing periodontally hopeless teeth, which might become a future research direction 45,47,50–53 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The local action of these factors results in cell survival, migration, proliferation and differentiation [14]. Due to these properties, PRF can be used to improve the regeneration of the replanted tooth by applying it directly to the socket or to protect the tooth outside the socket, thanks to the properties that reduce the death of PDL [15].…”
Section: Discussionmentioning
confidence: 99%